"COLD CHAIN" - EFFICIENCY AND SAFETY OF VACCINATION (World Bulletin of Public Health, 2022)
Vaccination is one of the greatest achievements of public health in the history of humanity. Vaccines used in national immunization programs are considered rational, safe and effective when used correctly. Immunization can prevent up to three million deaths worldwide from such controlled infectious diseases as measles, pneumonia, diarrhea, diphtheria and Covid-19, among others. This is one of the most cost-effective types of investments in healthcare. The Republic of Uzbekistan, together with UNICEF, WHO, GAVI, is working in an organized manner to improve the system of uninterrupted provision of vaccines, in compliance with the requirements of the cold chain
Keywords: Vaccine; Immunization; Cold Chain